Pengaruh Implementasi Good Government Governance Pada Kualitas Pelayanan Publik (Studi Pada Pemerintah Daerah Di Indonesia) - Shinta Sari; Ivan Yudianto; Sri Mulyani (Universitas Serang Raya, 2024)
This research aims to analyze the influence of governance implementation on the quality of public services. The research uses a quantitative research approach using secondary data from the 2022 regional government administration report. The results of the research show that of the 5 principles of good governance adopted from the principles issued by the KNKG, transparency, accountability, legal culture and equality and fairness have a significant effect and positive on the quality of public services at a significance level of 10%. Meanwhile, democratic principles do not have a significant effect on the quality of public services at a significance level of 10%. However, simultaneously good governance on the quality of public services shows a line coefficient of 0.813 with a p-value of 0.000. This means that good public governance has a significant and positive influence on the quality of public services at a significance level of 10% Keywords: Good Government Governance, Quality of Public Services